Studying changes in drought intensity and frequency in some parts of Syrian coastal region during the period 1960-2016 - سكاف ميشيل; بركات راما (Latakia University Journal -Biological Sciences Series, 2020)
Drought is considered as one of the most important extreme climatic events which adversely affecting the biosphere. Monthly precipitation and maximum and minimum temperatures data for three meteorological stations located in Syrian coastal region (lattakia-tartous-safita)were used during the period 1960-2016.Reconnaissance drought index (RDI) was applied to evaluate drought intensity at seasonal and annual time scales. Hargreves and Sammani equation was used to calculate potential evapotranspiration.Trends with Mann-Kendall test were used to detect changes in drought intensity. Whereas logistic distribution and differences in drought frequency were computed for two period 1960-1988 and 1988-2016, to estimate changes in drought frequency. Results showed significant increase in annual drought intensity owing to decreasing tendency in drought index values during spring and winter (ranging from 0.83 to 0.93 in spring) during the study period. Also results showed increasing in extreme and moderate drought frequency at the last decades. These changes in drought characteristics well pose a big challenges for water resources management and agricultural production in this region.